Alih Kode dan Campur Kode Pada Akun Twitter @Marnombois - Indah Suci Melati; Atiqa Sabardhila (Risenologi, 2022)
The problem reviewed in the research is alluding to code-switching and code-mixing on Twitter social media, along with the factors causing code-switching and code-mixing. The aim is to identify the form of code-switching and code-mixing in the @marnombois account tweets on Twitter social media using qualitative research. The data is taken from screenshots on tweet content that is following the title of the researcher. With qualitative research methods. The alteration of Javanese to Indonesian and Javanese to foreign languages is influenced by the user's background and several other social factors.